Validation of a simple model to predict the performance of methane oxidation systems, using field data from a large scale biocover test field. (October 2016) - Geck, Christoph; Scharff, Heijo; Pfeiffer, Eva-Maria; Gebert, Julia
Highlights: Efficiency of methane oxidation cover was 84% at up to 46 g CH4 m −2 d −1 . Prediction of oxidation potential using a simple model is promising. Use of capillary barrier as gas distribution layer caused upslope emissions. In an optimized cover direct emissions were not a permanent feature. Abstract: On a large scale test field (1060 m 2 ) methane emissions were monitored over a period of 30 months. During this period, the test field was loaded at rates between 14 and 46 g CH4 m −2 d −1 . The total area was subdivided into 60 monitoring grid fields at 17.7 m 2 each, which were individually surveyed for methane emissions and methane oxidation efficiency. The latter was calculated both from the direct methane mass balance and from the shift of the carbon dioxide - methane ratio between the base of the methane oxidation layer and the emitted gas. The base flux to each grid field was back-calculated from the data on methane oxidation efficiency and emission. Resolution to grid field scale allowed the analysis of the spatial heterogeneity of all considered fluxes. Higher emissions were measured in the upslope area of the test field. This was attributed to the capillary barrier integrated into the test field resulting in a higher diffusivity and gas permeability in the upslope area. Predictions of the methane oxidation potential were estimated with the simple model Methane Oxidation Tool (MOT) using soil temperature, air filled porosity and water tension as input parameters. It was found that the test field could oxidize 84% of the injected methane. The MOT predictions seemed to be realistic albeit the higher range of the predicted oxidations potentials could not be challenged because the load to the field was too low. Spatial and temporal emission patterns were found indicating heterogeneity of fluxes and efficiencies in the test field. No constant share of direct emissions was found as proposed by the MOT albeit the mean share of emissions throughout the monitoring period was in the range of the expected emissions.